Ketergantungan Petani terhadap Pendapatan Kelapa Sawit: Studi Kasus di Desa Manis Mata, Kecamatan Manis Mata, Kabupaten Ketapang - Nursaufi, Randy; Sudrajat, Jajat; Suharyani, Anita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The presence of oil palm plantations is known to have had a good economic impact on the region. However, on the other hand, it causes the dependence of farming households in rural areas on this single commodity. The purpose of this study is to determine the level of dependence of farming households in villages on oil palm farming income and the factors that affect it. To measure dependency we use a quantitative method with logistic regression. The data used consisted of primary data and secondary data. Primary data was obtained by interviewing 93 oil palm farmers. The results of the study show that the average dependence of farmer households on oil palm farming income reaches around 60%. This high dependence creates vulnerability when there is an income shock due to fluctuations in palm oil prices. The factors that significantly affect the dependence on oil palm income are the area of oil palm land and the variety of types of jobs owned by farmer households.